2005
DOI: 10.1111/j.1540-8167.2005.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Natriuretic Peptide Has Dose‐Dependent, Autonomically Mediated Effects on Atrial Refractoriness and Repolarization in Anesthetized Dogs

Abstract: ANP has dose-dependent, autonomically mediated effects on atrial refractoriness and repolarization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…The anti-inflammatory effect of RSD treatment may have relationship with the suppressed plasma levels of Ang II and aldosterone. ANP is released in response to atrial stretch, and studies suggested that ANP has dose-dependent, autonomically mediated effects on atrial refractoriness and repolarization and plays a role in atrial fibrosis of AF [31], [32]. In addition, Our present study suggests that RSD treatment could attenuate the increase in left atrial level of ANP that is induced by CRAP and could markedly alleviate the lesion degree of cardic fibrosis compared with the CRAP group, thus suppressing atrial remodeling.…”
Section: Discussionsupporting
confidence: 57%
“…The anti-inflammatory effect of RSD treatment may have relationship with the suppressed plasma levels of Ang II and aldosterone. ANP is released in response to atrial stretch, and studies suggested that ANP has dose-dependent, autonomically mediated effects on atrial refractoriness and repolarization and plays a role in atrial fibrosis of AF [31], [32]. In addition, Our present study suggests that RSD treatment could attenuate the increase in left atrial level of ANP that is induced by CRAP and could markedly alleviate the lesion degree of cardic fibrosis compared with the CRAP group, thus suppressing atrial remodeling.…”
Section: Discussionsupporting
confidence: 57%
“…Natriuretic peptide A-codifying gene has also been found mutated in AF, by altering the physiologic control exerted by this circulating hormone in the modulation of the neurohormonal stimulation and of ion channels [262][263][264][265]. A two-base-pair deletion was identified in the NPPA gene by Hodgson-Zingman and colleagues employing genomewide association study and pyrosequencing.…”
Section: Modeling Of Af-related Nppa Mutationsmentioning
confidence: 99%
“…In addition cardiac ion channels (sodium, potassium and calcium) are regulated by ANP through cGMP signaling 34,35,36 . ANP can promote AF either by shortening of the atrial action potential duration (APD) and effective refractory period (ERP), 37 or by autonomically-mediated shortening of the atrial monophasic action potential (MAP) duration and the ERP in dogs 38 . Therefore, it is hypothesized that NPPA mutation can lead to AF.…”
Section: Cardiac Developmental Pathwaysmentioning
confidence: 99%